J‐Shaped Association Between Postoperative Levothyroxine Dosage and Fracture Risk in Thyroid Cancer Patients: A Retrospective Cohort Study - Shin, Dong Wook; Suh, Beomseok; Lim, Hyunsun; Yun, Jae Moon; Song, Sun Ok; Park, Youngmin (Journal of bone and mineral research, 2018)
ABSTRACT Long‐term administration of supraphysiologic dosages of levothyroxine can have detrimental effect on the bone. We aimed to investigate fracture incidence among post‐thyroidectomy thyroid cancer patients compared with a matched comparison group, and explore the association between levothyroxine dosage and fracture risk. From the Korean National Health Insurance database, virtually all thyroid cancer patients who received thyroidectomy in Korea from January 1, 2004 to December 31, 2012 were included. Matched subjects were selected by 1:1 propensity score matching. Cox proportional hazards regression analysis was used to determine relative risk of osteoporotic fracture. Of 185,956 thyroid cancer patients identified, fracture events were observed in 1096 subjects (0.56%) over a mean 4.35 years of follow‐up. Compared to the matched comparison group, thyroid cancer patients had no elevated risk of osteoporotic fracture (hazard ratio [HR] 1.03; 95% confidence interval [CI], 0.94 to 1.12); however, the highest dosage group (≥170 μg/day) showed significantly higher risk (HR 1.25; 95% CI, 1.07 to 1.45), while the second quartile dosage group (115‐144 μg/day) showed lower risk (HR 0.71; 95% CI, 0.59 to 0.84) compared to a matched comparison group. When the second quartile dosage group was considered as reference, increased fracture risk was observed in those who took either lower (first quartile: adjusted HR 1.31; 95% CI, 1.08 to 1.59) or higher dosage of levothyroxine (third quartile: adjusted HR 1.50; 95% CI, 1.26 to 1.79; fourth quartile: adjusted HR 1.79; 95% CI, 1.51 to 2.13). Thyroid cancer patients were more likely to be treated with osteoporosis medication (HR 1.22; 95% CI, 1.18 to 1.26) than the matched comparison group. Both high and low dosage of levothyroxine treatment was associated with a higher risk for fractures in a J‐shaped dose‐dependent manner in post‐thyroidectomy patients. Future studies are needed to determine how to optimize thyroid‐stimulating hormone (TSH) suppression and how to screen and manage fracture risk. © 2018 American Society for Bone and Mineral Research.